Pengendalian Resiko K3 pada Industri Kecil Keripik TWM dengan Metode Job Safety Analysis - Nyoman Sri Widari; Lilis Nurhayati (Journal of Industrial View, 2024)
Abstract The TWM chip industry produces banana and cassava chips which are in great demand among the public. In this industry, most of the work is still done manually so that labor is the most important component in the production process. The problem encountered is that work accidents still occur quite frequently, where from the results of observations from May to October 2023, an average of 4,166 work accidents occurred. The aim of the research is to identify the risk of work accidents and provide control recommendations so as to reduce work accidents using the Job Safety Analysis method. Based on the results of data analysis, 14 potential dangers were found which were divided into 4 categories, namely the Low risk category 50%, Moderate risk 35.7% and the High risk category 14.3%, while the Extreme risk category did not exist. To reduce the number of accidents that occur, several recommendations that are recommended are the use of trolleys to move heavy loads, the need to use safety gloves when peeling and frying, the use of safety shoes, installing signs in places where accidents often occur, installing fire extinguishers and always checking the condition of the stove, gas cylinder and regulator before and after the frying process.  Abstrak Industri keci keripik TWM merupakan yang memproduksi keripik pisang dan keripik ketela yang banyak diminati oleh kalangan masyarakat. Di industri ini sebagian besar pekerjaannya masih dikerjakan secara manual sehingga tenaga kerja merupakan komponen terpenting dalam proses produksi. Permasalahan yang ditemui  adalah masih cukup sering terjadi kecelakaan kerja dimana dari hasil observasi selama bulan Mei sampai bulan Oktober 2023 terjadi kecelakaan kerja rata-rata 4,166 kasus.  Tujuan dari penelitian  adalah untuk melakukan identifikasi resiko kecelakaan kerja serta memberikan rekomendasi pengendalian sehingga dapat mengurangi kecelakaan kerja dengan menggunakan metode Job Safety Analysis. Berdasarkan hasil analisis data ditemukan 14 potensi bahaya yang terbagi dalam 4 katagori yaitu katagori Low risk 50% , Moderate risk 35,7% dan berkatagori High risk 14,3% sedangkan katagori Extreme risk tidak ada. Untuk menurunkan jumlah kecelakaan yang terjadi beberapa rekomendasi yang dianjurkan adalah pemakaian troli untuk memindahkan beban yang berat, perlunya pemakaian safety gloves pada saat pengupasan dan penggorengan, pemakaian safety shoes , memasang rambu rambu ditempat tempat yang sering timbul kecelakaan, pemasangan APAR dan selalu mengecek keadaan kompor , tabung gas dan regulator sebelum dan selesai melakukan proses penggorengan.